Mediating Role of Crisis Management between Knowledge Management and Employee Commitment - Abdalla Hassan sahako Aldhuhoor, Hassan; Din, Badariah binti Haji; Saoula, Oussama (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of the study is to examine the mediating role of crisis management between  knowledge management and employee commitment. Committed employees are needed to keep  the workforce motivated and knowledge is required to keep them committed, however, crisis issues  develop loyalty among the employees, and this can only be achieved if the employees effectively  manage knowledge. For the purpose of achieving the objectives of the study, primary study has  been conducted. A sample of 384 employees was used to run structural equation modeling. The  findings revealed that knowledge management has a significant impact over employee  commitment, likewise, crisis management significantly mediates the positive relationship between  knowledge management and employee commitment. The study used the underpinning support of  knowledge-based view, and it is an attempt to enrich the theory by adding crisis management in  the theory as a mediator.
Keywords: Crisis management; knowledge management; employee commitment